2006
DOI: 10.1074/jbc.m601443200
|View full text |Cite
|
Sign up to set email alerts
|

Histone H2A.z Is Essential for Cardiac Myocyte Hypertrophy but Opposed by Silent Information Regulator 2α

Abstract: In this study we have shown that the histone variant H2A.z is up-regulated during cardiac hypertrophy. Upon its knockdown with RNA interference, hypertrophy and the underlying increase in growth-related genes, protein synthesis, and cell size were down-regulated. During attempts to understand the mode of regulation of H2A.z, we found that overexpression of silent information regulator 2alpha (Sir2␣) specifically induced down-regulation of H2A.z via NAD-dependent activity. This effect was reversed by the protea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
64
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(71 citation statements)
references
References 27 publications
6
64
1
Order By: Relevance
“…Another point worth noting about the effects of PARP1 is that mild PARP1 activation has the potential to relax the chromatin structure, leading to activation of gene transcription [143]. PARP1 has also been shown to control the activity of a member of the class-III HDACs (SIRT1), which has been shown to have an antihypertrophy potential, thus further indicating that PARP1 may have a role in the regulation of MHC isoform switch during hypertrophy [139,144]. The role of PARP1 in cardiac disorders and that of its co-regulators in gene regulation have recently been reviewed [134,145,146].…”
Section: Chromatin Modifying Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another point worth noting about the effects of PARP1 is that mild PARP1 activation has the potential to relax the chromatin structure, leading to activation of gene transcription [143]. PARP1 has also been shown to control the activity of a member of the class-III HDACs (SIRT1), which has been shown to have an antihypertrophy potential, thus further indicating that PARP1 may have a role in the regulation of MHC isoform switch during hypertrophy [139,144]. The role of PARP1 in cardiac disorders and that of its co-regulators in gene regulation have recently been reviewed [134,145,146].…”
Section: Chromatin Modifying Enzymesmentioning
confidence: 99%
“…In addition, the effect of class-III HDACs (sirtuins, SIRT), which are also called longevity factors, needs to be examined for their potential to regulate MHC gene expression [150]. These proteins (SIRTs) have been shown to have anti-hypertrophic potential [144]. Also, many factors such as PARP1, Ku70, Nf-kB, and p300 that are known to participate in MHC gene regulation, and in the evolution of pathologic hypertrophy, have been shown to be targets of SIRT-dependent deacetylation [139,[151][152][153].…”
Section: Future Directionsmentioning
confidence: 99%
“…Some contradictory data have been published regarding the localization of each among different cell types: In 293 and HeLa cells, the 44-kDa form is nuclear and the 28-kDa form is present in both the nucleus and mitochondria (Scher et al 2007), whereas in mouse cardiomyocytes the 44-kDa form is found in the nucleus, mitochondria, and cytoplasm, and the 28-kDa form is exclusively mitochondrial (Sundaresan et al 2008). These differences are not surprising though, given that in rat cardiomyocytes SirT1-a nuclear protein in most cell lines-localizes to the nucleus in the embryo, to the cytoplasm in newborns, and to both the nucleus and cytoplasm in adults (Chen et al 2006). Nuclear SirT3 localizes to certain presently uncharacterized foci, and under stress conditions (e.g., UV irradiation, genotoxic stress, or SirT3 overexpression), relocalizes completely to mitochondria (Scher et al 2007).…”
Section: The Exertion Of Sirtuinsmentioning
confidence: 99%
“…For example, it is localized exclusively to the nucleus in male germ cells and in COS-7 cells transfected with SIRT1 cDNA (16,17). However, the cytoplasmic localization of SIRT1 has been reported recently in murine pancreatic ␤-cells and neonatal rat cardiomyocytes (19,20). Dynamic changes in the subcellular localization of Drosophila Sir2 during embryonic development have also been reported (21).…”
mentioning
confidence: 95%